Sustentación de caso: Propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Herrera Flores, Franco (2018)
The purpose of Sustainability of the case is to carry out a business analysis and strategic plain for a company in retail sector, within the fast fashion industry which wishes to enter the Peruvian market in 2019. In chapter 1 an analysis of the internal and external diagnosis of the Fast Fashion industry, detailing the business model, the value chain, competitive advantages, strengths and weaknesses in the internal analysis. Additionally, competitive forces, opportunities and threats and a PEST analysis will be detailed. Chapter 2 defines and supports the EFI matrix, EFE and generic strategies. The SWOT matrix, the mission, vision and strategic objectives of the company are introduced. Proposals for global, corporate, business, functional and redefinition strategies of UEN are presented. In the first section of chapter 3 an evaluation of redesign or not redesign of the organizational structure of the company is made and in the second section, a proposal for changes to improve the implementation of strategies. Chapter 4 presents a Strategic Control Map and a Balanced Scorecard for the company. Additionally, the conclusions, recommendations and references are exposed, where it is finally explained that the Peruvian market will respond favorably to the entry of Fast Retailing with its UNIQLO brand. Each developed point has a look from my perspective and professional experience over the years since my graduation from the house of studies in 2013. In a globalized world, where trends and technology rule, we as professionals in Administration must be constantly learning new ways of doing business, quickly adapt to new scenarios that may arise and, above all, seek permanent innovation. Finally, we must not lose sight of the role and impact of the company in society, as well as the fundamental values and principles that must govern the organization's management. Not only economic results should be expected, but those that are accompanied by social responsibility policies that generate a positive impact on the community.